VAPOUR-LIQUID EQUILIBRIUM IN SYSTEMS WITH ISOBUTYL ACETATE, ACETIC ACID AND METHYL ETHYL KETONE - V. I. Zhuchkov; S. L. Nazansky; O. N. Krupinova; A. K. Frolkova (Тонкие химические технологии)
The experimental temperature dependence of the vapour pressures of isobutyl acetate, acetic acid and methyl ethyl ketone were determined, and isobaric vapour-liquid equilibrium data of binary systems of methyl ethyl ketone + isobutyl acetate and methyl ethyl ketone + acetic acid were obtained. The experimental data were processed using the Antoine and Riedel equations and the NRTL and Wilson local composition equations, respectively. Comparison of the experimental and calculated data confirmed the adequacy of the vapour-liquid equilibrium mathematical simulation.